Subclinical seizures on stereotactic EEG: characteristics and prognostic value. (October 2022) - Cox, Benjamin C.; Khattak, Jamal F.; Starnes, Keith; Brinkmann, Benjamin H.; Tatum, William O.; Noe, Katherine H.; Van Gompel, Jamie J.; Miller, Kai J.; Marsh, W. Richard; Grewal, Sanjeet S.; Zimmerman, Richard S.; So, Elson L.; et al.
Highlights: Subclinical seizures are a common finding on stereotactic EEG, seen in 50% of our cohort Concordance between clinical and subclinical seizure onset zones does not predict surgical outcome Complete resection of subclinical seizure onset zone is associated with excellent surgical outcome. Subclinical seizures were more common in female patients than male patients during stereotactic EEG monitoring Abstract: Objective: Although stereotactic EEG (sEEG) has become a widely used intracranial EEG technique, the significance of subclinical seizures (SCS) recorded on sEEG is unclear and studies examining this finding on sEEG are limited. We investigated (1) the prevalence of SCS in patients undergoing sEEG and clinical factors associated with their presence, (2) how often the subclinical seizure onset zone (SOZ) colocalizes with clinical SOZ, (3) the association of SCS and surgical outcomes, and (4) the influence of resection of the subclinical SOZ on surgical outcome. Methods: We reviewed all patients who underwent intracranial monitoring with sEEG at our institution from 2015 through 2020 (n=169). Patient and seizure characteristics were recorded, as was concordance of subclinical and clinical seizures and post-surgical outcomes. Results: SCS were observed during sEEG monitoring in 84 of 169 patients (50%). There was no difference in the prevalence of SCS based on imaging abnormalities, temporal vs extratemporal SOZ, number of electrodes, or pathology. SCS were more common in females than males (62% vs 40%, p=0.0054). SCS had complete concordance with clinical SOZ in 40% of patients, partial concordance in 29%, overlapping in 19%, and discordant in 12%. Eighty-three patients had surgery, 44 of whom had SCS. There was no difference in excellent outcome (ILAE 12 or 2) based on the presence of SCS or SCS concordance with clinical SOZ; however, there were improved outcomes in patients with complete resection of the subclinical SOZ compared with patients with incomplete resection (p =0.013). Significance: These findings demonstrate that SCS are common during sEEG and colocalize with the clinical SOZ in most patients. Discordance with clinical SOZ does not necessarily predict poor surgical outcome; rather, complete surgical treatment of the subclinical SOZ correlates with excellent outcome. For unclear reasons, subclinical seizures occurred more commonly in females than males. Graphical abstract: Image, graphical abstract